Blended learning and technology model for teacher training in Cape Verde - Ramos, Fernando (2012)
This presentation addresses in detail the model developed for a 1400 basic school teachers training program in Cape Verde, that takes advantage from different technologies (Internet and radio) to support a blended learning solution adjusted to the real conditions of the trainees, most of them working in remote schools with neither electrical supply nor ICT infrastructure.